Given,

\(\displaystyle{\frac{{{3}+{5}{x}}}{{{5}}}}={\frac{{{4}-{x}}}{{{7}}}}\)

Step 2

On simplification, we get

\(\displaystyle\Rightarrow{7}{\left({3}+{5}{x}\right)}={5}{\left({4}-{x}\right)}\)

\(\displaystyle\Rightarrow{21}+{35}{x}={20}-{5}{x}\)

\(\displaystyle\Rightarrow{35}{x}+{5}{x}={20}-{21}\)

\(\displaystyle\Rightarrow{40}{x}=-{1}\)

\(\displaystyle\Rightarrow{x}=-{\frac{{{1}}}{{{40}}}}\)

\(\displaystyle{\frac{{{3}+{5}{x}}}{{{5}}}}={\frac{{{4}-{x}}}{{{7}}}}\)

Step 2

On simplification, we get

\(\displaystyle\Rightarrow{7}{\left({3}+{5}{x}\right)}={5}{\left({4}-{x}\right)}\)

\(\displaystyle\Rightarrow{21}+{35}{x}={20}-{5}{x}\)

\(\displaystyle\Rightarrow{35}{x}+{5}{x}={20}-{21}\)

\(\displaystyle\Rightarrow{40}{x}=-{1}\)

\(\displaystyle\Rightarrow{x}=-{\frac{{{1}}}{{{40}}}}\)